High-yielding rice Takanari has superior photosynthetic response to a commercial rice Koshihikari under fluctuating light - Adachi, Shunsuke; Tanaka, Yu; Miyagi, Atsuko; Kashima, Makoto; Tezuka, Ayumi; Toya, Yoshihiro; Kobayashi, Shunzo; Ohkubo, Satoshi; Shimizu, Hiroshi; Kawai-Yamada, Maki; Sage, Rowan F.; Nagano, Atsushi J.; et al. (Journal of experimental botany, 2019)
Leaves within crop canopies experience variable light over the course of a day, which greatly affects photosynthesis and crop productivity. Little is known about the mechanisms of the photosynthetic response to fluctuating light and their genetic control. Here, we examined gas exchange, metabolite levels, and chlorophyll fluorescence during the photosynthetic induction response in an Oryza sativa indica cultivar with high yield (Takanari) and a japonica cultivar with lower yield (Koshihikari). Takanari had a faster induction response to sudden increases in light intensity than Koshihikari, as demonstrated by faster increases in net CO₂ assimilation rate, stomatal conductance, and electron transport rate. In a simulated light regime that mimicked a typical summer day, the faster induction response in Takanari increased daily CO₂ assimilation by 10%. The faster response of Takanari was explained in part by its maintenance of a larger pool of Calvin–Benson cycle metabolites. Together, the rapid responses of electron transport rate, metabolic flux, and stomatal conductance in Takanari contributed to the greater daily carbon gain under fluctuating light typical of natural environments.